Effect of rest interval on cardiovascular responses after resistance exercise - Aluísio Henrique Rodrigues de Andrade Lima; Cláudia Lúcia de Moraes Forjaz; Gleyson Queiroz de Moraes Silva; Ana Paula Andrade Lima; Ozéas Lima Lins Filho; Crivaldo Gomes Cardoso Júnior; Raphael Mendes Ritti-Dias (Universidade Estadual Paulista (UNESP), 2013)
OBJECTIVE: To analyze the acute effect of rest interval length on cardiovascular response after resistance exercise. METHODS: Twenty young eutrophic men (23.9 ± 0.7 years;23.8 ± 0.5 kg/m²) performed two experimental sessions in a random order: resistance exercise with a 30-second (I30) and with a 90-second (I90) rest interval between sets. Both sessions included five exercises with 50% of the one-repetition maximum. Before and 24 hours after the experimental sessions, systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), and rate-pressure product (RPP) were obtained. RESULTS: The SBP, DBP and RPP responses were similar between the I30 and I90 sessions (p>0.05), while the HR after I30 was significantly higher than after I90 (p<0.01) for the first hour after exercise. The cardiovascular responses during the first 24 hours were similar between both sessions (p>0.05). CONCLUSION: Different recovery intervals did not promote post-exercise hypotension, however, a short rest interval increases heart rate for 1 hour after exercise. In addition, within 24 hours of the responses were similar between groups.